Requirements Engineering Practices in UUMIT Centre: An Assessment Based on the Perceptions of In-House Software Developers - Hussain, Azham; Mkpojiogu, Emmanuel O.C; Abdullah, Inam (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Requirements Engineering (RE) is a systematic procedure that entails and encompasses the elicitation, elaboration, documentation, negotiation, validation and management of the system’s requirements in a software engineering project. Universiti Utara Malaysia (UUM) is been supported by several systems, engineered by the UUM Information Technology (UUMIT) Centre. The objective of this paper was to investigate the requirements engineering practices at UUMIT Centre. The major issue that led to this study was the absence of studies that support software development efforts at the UUMIT Centre. This research is aimed at assisting UUMIT Centre in developing quality, and as well, time and cost saving software systems through the employment of state of the art requirements engineering practices. Furthermore, the paper, as a contribution to UUM, identifies the activities that are needed for software construction to enable the University management allocate budget for the provision of adequate and cutting edge training for the in-house software developers. Three variables were assessed: Requirement Description, Requirements Development (consisting of: Requirements Elicitation, Requirements Analysis and Negotiation, Requirements Validation), and Requirement Management. The results from this research revealed that the current practices of requirement engineering in UUMIT is good and commendable, however there is need and room for more improvement in a few RE practices that were rarely practiced. In addition, recommendations were also proffered for effective training programs for UUMIT staff on RE practices to build the capacity of in-house developers and other associated staff. The training will increase their understanding on system requirements using RE practices to enable them develops better systems for the university. Further investigation is required in the future to understand the effect of RE practices on software development. In addition, also as a future work, the researchers aim to extend the scope of this study to other government and non-educational organizations